IMPORTANCE EDUCATION SOUL LEADERSHIP IN PREVENTION BULLYING HAPPENED AMONG STUDENT SCHOOL MEDIUM FIRST (British Journal of Global Ecology and Sustainable Development, 2022)
Bullying is the act of using power to hurt a person or group of people either verbally, physically or psychologically so that the victim feels pressured, traumatized and helpless (Sejiwa, 2008). Adolescents who are victims of bullying are more at risk of experiencing various health problems, both physically and mentally. The problems that are more likely to be suffered by children who are victims of bullying include the emergence of various mental problems such as depression, anxiety and sleep problems that may carry over into adulthood, physical health complaints, such as headaches, stomach aches and muscle tension, feeling unwell. safe while in the school environment, and decreased enthusiasm for learning and academic achievement. In quite rare cases, children who are victims of bullying may show violent traits. As experienced by a 15-year-old teenager in Denpasar, Bali, who had the heart to kill his own friend because of his grudge against the victim.